Student Emotions in Online Foreign Language Instruction - Budzińska, Katarzyna (Research in Language, 2025)
Emotions in educational settings can profoundly influence students’ learning and achievement (Pekrun, 2014). Despite the recent increase in interest in foreign language student emotions, emotions in the field of online education remain underresearched (Kruk & Pawlak, 2022). The global shift to emergency remote teaching in response to the COVID-19 pandemic has drawn researchers’ attention to the emotions experienced by learners whose classes were unexpectedly moved online. Thus far, studies have mainly focused on anxiety, enjoyment, and boredom, while other emotions have not been sufficiently explored. This qualitative study examines the full range of emotions experienced by learners, as well as the factors responsible for those emotions. A total of 218 university learners of English, German, Italian, and French participated in the research. Data were collected via an online questionnaire and semi-structured interviews. Participants were found to experience interest, enjoyment, frustration, anxiety, boredom, pride, shame, helplessness, anger, serenity, relief, sadness, and envy. The most frequently mentioned emotion was interest, followed by enjoyment and frustration.